2019
DOI: 10.1177/0969141319877669
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of risk-stratified breast screening: Effect of the order of presenting risk and benefit information

Abstract: Objective To test whether reduced-frequency risk-stratified breast screening would be perceived more favourably by transposing the order of information on benefits and risks. Methods After reading vignettes describing non-stratified three-yearly screening and a risk-stratified alternative with five-yearly invitations for women at low risk, 698 women completed an online survey. Participants were allocated at random to information on screening benefits followed by risks, or vice versa, and asked to state prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…They found that participants were divided over the use of both age or a risk score, with 22% and 24.3% respectively responding that using age or a risk score was not at all reasonable and 16.3% and 11.3% responding that each was extremely reasonable. Age was considered more reasonable overall than using a risk score in that study, although that may reflect a preference for status quo that has been reported in previous studies 24 …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…They found that participants were divided over the use of both age or a risk score, with 22% and 24.3% respectively responding that using age or a risk score was not at all reasonable and 16.3% and 11.3% responding that each was extremely reasonable. Age was considered more reasonable overall than using a risk score in that study, although that may reflect a preference for status quo that has been reported in previous studies 24 …”
Section: Discussionmentioning
confidence: 87%
“…In general, these have found that members of the public are positive towards being offered more screening but are concerned about the possibility of less screening. [24][25][26][27] Although a significant proportion of participants in this study were uncomfortable about only men having screening and a significant proportion of women uncomfortable about having to wait until they were older than men for screening, most (>70%) were comfortable waiting until they were older to start screening if they were low risk when that risk was based on a risk score or genetic risk. It is possible that delaying the start of screening based on risk scores may be more acceptable than extending the interval between screening episodes.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
See 1 more Smart Citation
“…This suggests that communication strategies need to be identified that are sensitive to differences between invitees in terms of their subjective interpretation of their risk status. 32 Understanding people’s preferences for different intervals, and modalities could also be explored further through in-depth interviews and more systematic discrete choice experiments which could be used to test the extent to which people are willing to trade different aspects of CRC screening, for example, convenience for other characteristics such as test sensitivity. These studies could then ensure high levels of acceptance and uptake and thereby potentially reduce the potential for widening inequalities if studies are performed with representative samples which include lesser heard groups.…”
Section: Public Attitudes Towards Risk-adaptive Screeningmentioning
confidence: 99%
“…Most such studies compare screening benefits with one harm, either false alarms or unnecessary treatment. [13][14][15][16][17] Ghanounia et al 18 asked women about all 3 outcomes, but without providing quantitative estimates of their probabilities.…”
mentioning
confidence: 99%